2006
DOI: 10.1111/j.1365-2044.2006.04707.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of organ failures and their relationship with outcome in intensive care: analysis of a prospective multicentre database of adult admissions

Abstract: SummaryThe database of a multicentre cohort study was analysed to determine the impact of intensive care unit (ICU) organ failures and their association with ICU mortality using sequential organ failure assessment (SOFA). A consecutive sample of 873 adult patients with a non‐neurological diagnosis was identified. SOFA scores were measured every 24 h of ICU stay. The odds of ICU death within 7 days doubled (95% CI 1.3–2.9) for a 5‐unit increase in total SOFA score at admission, p < 0.001. However ICU death a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 23 publications
3
30
0
Order By: Relevance
“…Goldhill and Sumner (1998) reported that 23.8% of 12,762 patients admitted to 15 British ICUs died. Similar figures (26.6%) were reported from a prospective multicenter trial which included 873 ICU patients (Nfor et al 2006). Moreover, many patients died after discharge from ICU.…”
Section: Introductionsupporting
confidence: 85%
“…Goldhill and Sumner (1998) reported that 23.8% of 12,762 patients admitted to 15 British ICUs died. Similar figures (26.6%) were reported from a prospective multicenter trial which included 873 ICU patients (Nfor et al 2006). Moreover, many patients died after discharge from ICU.…”
Section: Introductionsupporting
confidence: 85%
“…In critical illness other than ALF the presence of systemic cardiovascular dysfunction is of major prognostic importance, and in this setting indicates the overall severity of MOF [23]. The requirement for vasopressors may also reflect evolving sepsis and be associated with compromised early graft perfusion, and it is perhaps no surprise that outcome was worse in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the application of sepsis protocols, mortality rate is still high in septic ICU patients, particularly in the septic shock and multi-organ failure patients [16,24,25]. In addition to classical sepsis protocols, there are many adjunctive therapies in severe sepsis to reduce the mortality further [3].…”
Section: Discussionmentioning
confidence: 99%